Thermographic skin temperature response to different movement velocity of squat exercise until exhaustion: A prelimninary report - Formenti, D.; Trecroci, A.; Ludwig, N.; Gargano, M.; Caumo, A.; Alberti, G. (19th Annual Congress of the European College of Sport Science (ECSS), Amsterdam, 2. - 5. July 2014, 2014)
INTRODUCTION: Blood flow restriction resistance training is an effective training method for improving muscular function using low and moderate load intensity (Alberti et al., 2013). It has implications in the regulation of skin blood flow, with important consequence for the blood involved in heat dissipation through the skin. The aim of this study was to investigate the skin temperature (ST) response by using infrared thermography during slow speed low intensity exercise as compared to normal speed low intensity exercise in squat trial (Tanimoto et al., 2006). We hypothesized that low intensity resistance exercise with slow movement would result in a ST response slower than the one of the normal speed exercise with the same intensity. METHODS: 9 active males (23.6±1.1yrs, 69.7±6.8kg, 176±6.2cm) performed 2 sessions of deep squat exercise until exhaustion, with 50% of 1 RM. The pace of movement was set in 1s eccentric / 1s concentric and 5s eccentric / 5s concentric phase in the 1st and in the 2nd session respectively. Thermal images were recorded every 20s before exercise (2min), during exercise (until exhaustion), and after exercise (10min). dT (Tpeak-Tbasal) and Time50% (time to reach 50% of dT) were identified and compared in 1s vs 5s trials by using paired t-test. RESULTS: Surprisingly, a different behaviour of ST during and after exercise was observed among subjects: a decrease in ST in 5 subjects (down group) and an increase in the other 4 (up group). Thus, statistics was performed in each group separately. The dT of the up group in 1s (1.1±0.42°C) and 5s (1.0±0.50°C) were approximately twice that of the down group in both 1s (-0.50±0.15°C) and 5s (-0.42±0.28°C). The dT in 1s was similar to dT in 5s in both groups. The ST changes (Time50%) in the down group occurred slowly (p<0.01) in 1s (30.1±17.2s) vs 5s (107.3±25.3s) as well as in the up group (139.1±17.2s in 1s vs 184.9±58s in 5s; p>0.05). The ST changes during 1s and 5s trials occurred more rapidly in the down group than in the up group. DISCUSSION: It was shown that the response of cutaneous circulation to dynamic exercise is characterized by a initial vasoconstriction to dissipate heat from the core through the skin followed by vasodilation driving the blood flow from inactive tissue (including the skin) to active muscles involved in exercise (Kellogg D.L., 2006). We speculate that the unexpected different behaviour of the ST response in the 2 groups was probably due to a time-dependent predominance of vasoconstriction over vasodilation or viceversa.